Enhancing FDI Flows to Nepal during the Period of Post-conflict Transition and Global Recession - Pant, Bhubanesh (NRB Economic Review, 2010)
FDI is much sought after in conflict-stricken countries such as Nepal as it can play a crucial role in the development process. However, the process of attracting and promoting FDI is complex, in particular as most developing countries, including Nepal, are competing for similar types of FDI. Although a number of efforts have been made in the past to boost FDI flows to the country, they have not had any striking impact. The country has not been able to draw on the potential technological and other contributions that FDI can make to the process of development. This underlines the need for effective policy interventions with a view to maximizing the benefits of FDI for Nepal's development in an open environment. Nepal also needs policy framework to enhance national and regional infrastructure, in areas such as transport, energy and communications services, and to generate domestic employment and skills transfer. The main policy conclusion that can be drawn from this paper is that the economic benefits of FDI are real, but they do not accrue automatically. To reap the maximum benefits, a healthy enabling environment for business is paramount, which encourages domestic as well as foreign investment, provides incentives for innovation and improvements of skills and contributes to a competitive investment climate.